NIMG-62. AMPHETAMINE-ASSOCIATED CNS VASCULITIS MASQUERADING AS TUMOUR. (9th November 2020) - Shivaprasad, Akhil; Qasim, Muhammad; Langford, Lauren; Fuller, Gregory; El-Naggar, Adel K; Vishwanathan, Ashwin; Tremont-Lukats, Ivo; Majd, Nazanin
Abstract: Amphetamine-associated CNS vasculitis is controversial. There are few reports but none as a tumor mimic to our knowledge. We describe a pathology-proven, amphetamine-associated CNS vasculitis resembling a tumor. A 41-year-old man presented with six weeks of progressive confusion and left-sided weakness. CT head reported a right thalamic mass with vasogenic edema. Laboratory tests were unremarkable except for cannabinoids and amphetamine in urine. MRI brain showed enhancement in right frontotemporal lobe, basal ganglia, and thalamus concerning for glioblastoma multiforme. After high-dose IV dexamethasone, an initial biopsy showed reactive gliosis, perivascular lymphocytic cuffing by CD3+, rare CD20+ cells and no infection. He continued to decline. MRI 22 days after admission showed increased T2/FLAIR hyperintensity, multifocal areas of enhancement, microhemorrhages, and ischemia. High-grade glioma, lymphoma and infectious encephalitis remained on differentials. Treatment included broad-spectrum antibiotics and acyclovir. Biopsy on 23rd day showed reactive gliosis with parenchymal macrophage infiltration and perivascular cuffing with mixed inflammatory infiltrates. CSF: slightly elevated WBCs (8/µL), elevated protein (139mg/dL), normal glucose, and no infection. MRI whole spine and CT body were unremarkable. The patient was transferred to MDACC 5.5 weeks after initial presentation. He was alert with expressive aphasia, right gaze preference, left hemiplegia, and right hemiparesis. He underwent a right anterior temporal lobectomy. Pathology showed extensive cortical laminar and white matter necrosis with macrophage infiltration and microglial activation. In areas of the preserved cortex, vasculocentric lymphocytic aggregates were present and reticulin staining showed lymphocytic infiltration of the vascular walls. Immunophenotyping (CD3, CD20) showed an almost pure T-cell population. The predominance of intramural T-lymphocytes reflected a vasculitic process. The final diagnosis was cerebral vasculitis with subacute infarction. The patient died six days later. The autopsy findings were identical to the previous resection without evidence of systemic inflammation.